Adrenal adrenoceptors in heart failure - de Lucia, Claudio; Femminella, Grazia D.; Gambino, Giuseppina; Pagano, Gennaro; Allocca, Elena; Rengo, Carlo; Silvestri, Candida; Leosco, Dario; Ferrara, Nicola; Rengo, Giuseppe (Frontiers in Physiology, 2014)
Heart failure (HF) is a chronic clinical syndrome characterized by the reduction in left ventricular (LV) function and it represents one of the most important causes of morbidity and mortality worldwide. Despite considerable advances in pharmacological treatment, HF represents a severe clinical and social burden. Sympathetic outflow, characterized by increased circulating catecholamines (CAs) biosynthesis and secretion, is peculiar in HF and sympatholytic treatments (as β-blockers) are presently being investigated for the treatment of this disease. Adrenal gland secretes Epinephrine (80%) and Norepinephrine (20%) in response to acetylcholine stimulation of nicotinic cholinergic receptors on the chromaffin cell membranes. This process is regulated by adrenergic receptors (ARs): α2ARs inhibit CA release through coupling to inhibitory Gi-proteins, and βARs (mainly β2ARs) stimulate CA release through coupling to stimulatory Gs-proteins. All ARs are G-protein-coupled receptors (GPCRs) and GPCR kinases (GRKs) regulate their signaling and function. Adrenal GRK2-mediated α2AR desensitization and downregulation are increased in HF and seem to be a fundamental regulator of CA secretion from the adrenal gland. Consequently, restoration of adrenal a2AR signaling through the inhibition of GRK2 is a fascinating sympatholytic therapeutic strategy for chronic HF. This strategy could have several significant advantages over existing HF pharmacotherapies (antiadrenergic, such as bAR-blockers) minimizing side-effects on extra-cardiac tissues and reducing the chronic activation of the renin–angiotensin–aldosterone and endothelin systems. The role of adrenal ARs in regulation of sympathetic hyperactivity opens interesting perspectives in understanding pathophysiology of HF and identifying new potential therapeutic targets.